2013
DOI: 10.1186/2041-7136-3-18
|View full text |Cite
|
Sign up to set email alerts
|

Caught in a sandstorm: an assessment of pressures on communal pastoral livelihoods in the Kalahari Desert of Botswana

Abstract: Despite their importance to rural livelihoods, the economic and environmental sustainability of contemporary communal pastoral systems of the Kalahari is increasingly being put under scrutiny. Using data collected from a survey of randomly selected pastoral households from two districts of Ghanzi and Kgalagadi South, Botswana, this paper outlines the major constraints affecting contemporary extensive pastoral systems. Because of the prevailing semi-arid climate, recurrent drought outbreaks were cited as a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The constraint is common amongst all the villages surveyed. Mosalagae and Mogotsi (2013) reported that pastoral farmers in Botswana lose livestock due to predation. Theft was ranked the second important constraint.…”
Section: Production Constraints That Impede Farmers From Maximizing Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The constraint is common amongst all the villages surveyed. Mosalagae and Mogotsi (2013) reported that pastoral farmers in Botswana lose livestock due to predation. Theft was ranked the second important constraint.…”
Section: Production Constraints That Impede Farmers From Maximizing Tmentioning
confidence: 99%
“…Theft was ranked the second important constraint. In Kgalagadi south, Botswana, pastoral households reported to be facing the problem of theft (Mosalagae and Mogotsi, 2013). Ranked third in the area were livestock diseases.…”
Section: Production Constraints That Impede Farmers From Maximizing Tmentioning
confidence: 99%
“…Malekano (2000) reported poverty to be the prime cause of livestock theft in Malawi. The study by Mosalagae and Mogotsi (2013) in Gantsi and Kgalagadi districts of Botswana identified the five most important constraints in livestock production to be drought, predation, inadequate drinking water for livestock, limited grazing land, loss of livestock due to road accidents and theft.…”
Section: Introductionmentioning
confidence: 99%
“…Such absentee farmers, often termed 'remote control farmers' , may reside either in villages or towns, away from their livestock at the cattle posts, and rarely check on the welfare of both their livestock and hired herders (Mosalagae and Mogotsi 2013). The latter would also, upon realizing the neglect shown by their employers, either be de-motivated to continue tending to the animals (mostly watering, herding and general routine management) or worse abandon the animals.…”
Section: Apathymentioning
confidence: 99%
“…According to the Government of Botswana (2011), livestock theft in Botswana has generally been on the rise in the recent past, thus prompting establishment of an Anti-Stock Theft Unit within the Police Service in order to curb this crime, coupled with other pertinent legislation such as the Stock Theft Act (1996). While livestock theft has been observed as a challenge to livestock producers in other parts of the country (Mosalagae and Mogotsi 2013) and in other countries in the region such as Lesotho (Kynoch and Ulicki 2000), Malawi (Malekano 2000), Swaziland (Simelane 2005), South Africa (Kunene and Fossey 2006), Zimbabwe (Mavedzenge et al 2008) and Namibia (Olbrich et al 2012), it is even more complex in areas bordering other countries since it involves increased exposure to risks such as economically devastating transboundary diseases like FMD.…”
Section: Livestock Theftmentioning
confidence: 99%